Advances in cancer research. - Tew, Kenneth D.; Fisher, Paul B. (Advances in cancer research, 2018)
Advances in Cancer Research, Volume 138, the latest release in this ongoing, well-regarded serial provides invaluable information on the exciting and fast-moving field of cancer research. This volume presents original reviews on research bridging oncology and gene expression, with this volume covering unconventional approaches to modulating the immunogenicity of tumor cells, tumor dormancy and immunoediting, the emerging role of anti-apoptotic Bcl-2 family proteins in chemoresistance, Beclin-1 and autophagy, MDA-7/IL-24, and nanotechnology and medicine.